Al-Quran dan Budaya Profetik: Mencetak Insan Kamil di Era Milenial - Nur Alfiana; Wahyu Budiantoro (Intiqad: Jurnal Agama dan Pendidikan Islam, 2021)
Document this study aims to identify and explain the prophetic concept in the Qur'an and its relevance in shaping the personality of human beings in the millennial era, especially in the area of education. This study uses a qualitative method. Data sources are divided into two, primary and secondary. Primary data were obtained from verses of the Qur'an which talk about the concept of prophetic and insan kamil. While secondary data was obtained from several scientific journals and books that talk about similar themes. The results of the study are, firstly, the Qur'an contains many prophetic and human concepts, secondly, the Qur'an also talks about the concept of education in prodemic culture, and thirdly, the great qualities of the Prophet Muhammad such as sidiq, amanah, fatah, become guidelines for millennials to develop human personality